Electrocatalytic acidic oxygen evolution reaction: From nanocrystals to single atoms. Issue 4 (2nd August 2021) - Ismail, Nadia; Qin, Fengjuan; Fang, Chaohe; Liu, Dan; Liu, Bihan; Liu, Xiangyu; Wu, Zi‐long; Chen, Zhuo; Chen, Wenxing
Abstract: Hydrogen is the most preferred choice as an energy source to replace the nonrenewable energy resources such as fossil fuels due to its beneficial features of abundance, ecofriendly, and outstanding gravimetric energy density. Splitting water through a proton exchange membrane (PEM) electrolyzer is a well‐known method of hydrogen production. But the major impediment is the sluggish kinetics of oxygen evolution reaction (OER). Currently, scientists are struggling to build out an acid‐stable electrocatalyst for OER with low overpotential and excellent stability. In this review, the reaction mechanism and characterization parameters of OER are introduced, and then the improvement method of metal nanocatalysts (noble metal catalysts and noble metal‐free catalysts) in acidic media is discussed. Particularly, the application of single‐atom catalysts in acidic OER is summarized, which is current researching focus. At the same time, we also briefly introduced the cluster phenomenon, which is easy to occur in the preparation of single‐atom catalysts. More importantly, we summarized the in situ characterization methods such as in situ X‐ray absorption spectroscopy, in situ X‐ray photoelectron spectroscopy, and so forth, which are conducive to further understanding of OER reaction intermediates and active sites. Finally, we put forward some opinions on the development of acidic OER. Abstract : Facing the challenge of slow reaction kinetics of acidic OER, electrocatalysts with excellent performance and cost‐effective are urgently needed. The structure of nanocrystalline catalysts can be carefully controlled by atomic interface engineering, and in situ characterization techniques prove that single‐atom catalysts endow with excellent catalytic performance so that can fulfill the desired criteria to better extent.